Change in serum interleukin-6 levels in patients after pancreatoduodenectomy for periampullary cancer (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
This study was undertaken to elucidate the changes in interleukin-6 concentrations in the systemic circulation of 20 patients following pancreatoduodenectomy and whether it had any predictive value for postoperative complications. Blood was drawn on the day before surgery, at fixed intervals immediately after closure of the abdomen, and on day 1, 3, 5 after surgery for the measurement of interleukin-6. Change in the serum interleukin-6 levels was observed before and after pancreatoduodenectomy and between patients with and without complications. There was no mortality, but morbidity occurred in 5 patients. Serum interleukin-6 levels peaked immediately after surgery and gradually declined to preoperative level on postoperative day 5, but it remained persistently higher in a patient who developed postoperative complication. The peak level of interleukin-6 was significantly correlated with body mass index, duration of jaundice, biliary decompression prior to surgery, operation time and hospital stay, but not with operative blood loss. In conclusion, interleukin-6 is an important stress marker for predicting the complications after pancreatoduodenectomy operation. Patient with good body mass index status, short duration of jaundice and without preoperative biliary decompression provides less operative stress, less chance of complications and shorter hospital stay.